The Third Cognitive Revolution: The consequences and possibilities for biomedical research - Hittner, James B (EMBO Rep, 2019)
The Third Cognitive Revolution poses particular challenges for biomedical research to adopt new knowledge. Interdisciplinary education at all levels would help to address these.[Image: see text]